Hubungan Kompetensi Spritual dan Motivasi Mengajar Guru PAK Dengan Prestasi Belajar PAK Siswa SMP Swasta HKBP Sibolga Tahun Pembelajaran 2019/2020 - Tarida Hetting Silitonga (Jurnal Euangelion, 2021)
The research objectives were to determine: 1) a positive and significant relationship between spiritual competence and learning achievement, 2) a positive and significant relationship between PAK teachers' teaching motivation and learning achievement, c) a positive and significant relationship between spiritual competence and teaching motivation together with learning achievement. Research hypotheses: 1) there is a positive and significant relationship between spiritual competence and learning achievement, 2) there is a positive and significant relationship between PAK teachers' teaching motivation and learning achievement, 3) there is a positive and significant relationship between spiritual competence and teaching motivation together with learning achievement. The research was analyzed: 1) tcount = 5.413> ttable = 2.021 there was a positive and significant relationship between spiritual competence and learning achievement in the strong category, 2) tcount = 5.508> t table = 2.021 there was a positive and significant relationship between PAK teachers' teaching motivation and learning achievement in the strong category , 3) multiple correlation value tcount = 11.295> ttable = 2.021 there is a positive and significant relationship between spiritual competence and teaching motivation of PAK teachers together with strong category learning achievement.